THE INFLUENCE OF E-COMMERCE DIGITAL MARKETING IN DEVELOPING LOCAL BRANDS IN INDONESIA (STUDY AT PT. BUKA LAPAK.COM Tbk) - T. Nurhaida; Lilinesia; Emy Yatul Hasanah (RADJA PUBLIKA, 2023)
The internet is something that is familiar to the ears of the Indonesian people. Internet usage in Indonesia from year to year has increased very significantly. From the survey results of the Indonesian Internet Service Providers Association (APJII), internet users in Indonesia for the 2022-2023 period have reached 2016.63 million people. This number increased compared to the 2021-2022 period of 2.67%, namely 210.03 million users. This journal discusses the influence of e-commerce digital marketing in developing local brands in Indonesia. The research methods used in this study are qualitative, descriptive and literature studies. The ability to master digital marketing is very important in building a brand and also in marketing products. No wonder nowadays many foreign brands and local brands are starting to follow the development of the times, cooperation between local e-commerce and local brands will have a very good impact on both parties.